Предмет: Алгебра,
автор: richiDL
1/(х-1)^2 + 2/х-1 -3=0
Ответы
Автор ответа:
0
ОДЗ
х-1≠0
х≠1
Пусть 1/(х-1)=у, тогда
у²+2у-3=0
D=4+4*3=16
у₁=(-2+4)/2=1
у₂=(-2-4)/2=-3
1/(х-1)=1
х-1=1
х₁=2
1/(х-1)=-3
х-1=-1/3
х=-1/3+1
х₂=2/3
Ответ (2; 2/3)
х-1≠0
х≠1
Пусть 1/(х-1)=у, тогда
у²+2у-3=0
D=4+4*3=16
у₁=(-2+4)/2=1
у₂=(-2-4)/2=-3
1/(х-1)=1
х-1=1
х₁=2
1/(х-1)=-3
х-1=-1/3
х=-1/3+1
х₂=2/3
Ответ (2; 2/3)
Похожие вопросы
Предмет: Информатика,
автор: antongangsta77
Предмет: Математика,
автор: Veronikaa464268
Предмет: Английский язык,
автор: bdavydenko10
Предмет: Математика,
автор: bhbr1972
Предмет: География,
автор: djulilienko27